Islamic Education and Human Construction in The Quran - Azis Abdullah; Siswanto Masruri; Khoiruddin Bashori (Association for Scientific Computing Electrical and Engineering(ASCEE), 2019)
This research patterned literature by examining and tracing various literature, relating to human construction in the Koran. Research findings that humans from the creation process have various potentials and functions of life in this world. So that humans have a position of choice, the best human being and the main human being. The human position of choice is in words, namely: mukhlason (clean / choice), al-Mushthofaina (chosen people), and al-Khiyarah (choice). The best human position is found in the word al-husna (best) and husnu (the best). The process of relevance and development with the world of education, that education as a strategic means aims to develop or cultivate the basic physical and spiritual abilities of humans as caliphs.